Expectations of the doctor in a private hospital--phase 2 - Klopper, H C (Curationis (Pretoria), 1994)
The purpose of this phase of the study was to explore and describe the expectations of the doctor in a private hospital with regard to the registered nurse's practice (phase 2). The expectations of the doctor were explored by means of a explorative and descriptive design. A questionnaire was designed as a data-gathering instrument, based on the scope of practice of the registered nurse (described in the conceptual framework). Through the use of descriptive statistics, a frequency-analysis was done and reflected through the use of percentages. The results were discussed in detail and presented in tables. To summarize the results, fifteen conclusion statements were described, out of which data for the orientation programme was inferred (phase 3).